The Correlation Of Mother's Knowledge And Work With The Incidence Of Anemia In Pregnancy At The Modesta Clinic, Sinaman Village, Barusjahe District, Karo District, 2023 - Ginting, Kristinawati Br; Silalahi, Imelda Sarwani Br; Eva Ratna Dewi; Simbolon, Marlina; Manurung, Basaria; Simanjuntak, Markus Doddy (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2023)
The global incidence of anemia in 2019 in women of childbearing age was 29.9% in women of childbearing age, equivalent to more than half a billion women aged 15-49 years. Meanwhile, 29.6% of non-pregnant women of childbearing age were pregnant, and 36.5% of pregnant women. The aim of this research is to determine the relationship between maternal knowledge and occupation and the incidence of anemia in pregnancy at the Modesta Clinic, Sinaman Village, Barujahe District, Karo Regency in 2023. This research design uses a descriptive research design with a cross-sectional quantitative approach. This research was carried out in April-July 2023. The research population was all pregnant women who visited and were hospitalized at the Modesta Clinic, Sinaman Village, Barusjahe District, Karo Regency. The population is 47 people. Purposive sampling technique is a technique that determines certain criteria for the sample. The results of statistical tests using the Chi Square test that were carried out showed a p value of 0.004 (p<0.05) which shows that there is a relationship between knowledge and the incidence of anemia in pregnancy at the Modesta Clinic, Sinaman Village, Barusjahe District, Karo Regency in 2023. Further research is needed. related to other factors related to anemia so that better treatment can be found. Midwives and health workers provide IEC and counseling about anemia in pregnancy.